Your Mileage May Vary: Case Study of a Robotic Telepresence Pilot Roll-out for a Hybrid Knowledge Work Organisation - Boudouraki, Andriana; Fischer, Joel E.; Reeves, Stuart; Rintel, Sean (CHI 2023, 2023)
Organisations wishing to maintain employee satisfaction for hybrid collaboration need to explore flexible solutions that provide value for both remote and on-site employees. In this case study, we report on the roll-out of a telepresence robot pilot at Microsoft Research Cambridge UK to test whether robots would provide enjoyable planned and unplanned encounters between remote and on-site employees. We describe the work that was undertaken to prepare for the roll-out, including the Occupational Health and Safety assessment, systems for safety and security, and the information for employees on safe and effective use practices. The pilot ended after three months, and robot use has been discontinued after weighing the opportunities against low adoption and other challenges. We discuss the pros and cons within this organisational setting, and make suggestions for future work and roll-outs.